3D modeling of salt domes according to detailed drilling data in the Precaspian region - V. V. Lapkovsky; B. V. Lunev; M. P. Antipov; Yu. A. Volozh; Yu. A. Pisarenko; V. V. Fomina (Georesursy, 2024)
To create three-dimensional models of arcomorph structures based on detailed data of drilling without involving genetic considerations and indirect information, the potential fields method is effective, which consists of finding an approximating three-dimensional function, the set of isolevel surfaces of which are identified with stratigraphic boundaries, using the coordinates of the formation intersection points. For approximation, mainly three-dimensional splines expressed in terms of Green’s functions were used. The main difficulties are associated with the presence of structural unconformities, to take into account which the initial data, and the models built on their basis, are subjected to special spatial transformations. To avoid the influence of high-amplitude arcomorphs on the geometry of the layers of the pre-salt complex, the modeling of the latter was carried out separately from the intensely deformed evaporates and overlying layers. Assaying of the method was carried out at one of the sites in the Caspian Sea. On the study area, according to the interpretation of logging data from 249 wells, a three-dimensional model was created, including several arcomorph structures, and covering the stratigraphic interval from the Emsian stage of the Lower Devonian to Quaternary deposits. The results confirmed the presence of arcomorphs with overturned beds. Such structural forms are poorly fixed by 2D–3D seismic survey methods. The proposed method can be applied in geological studies in the search and exploration of hydrocarbons in salt dome areas.